A study on the health economics of general practitioners in Malaysia: trends, challenges and moving forward - Kenny, Kamal; Omar, Zoharah; Kanavathi, El Sheila; Madhavan, Priya (Department of Community Health, Universiti Kebangsaan Malaysia Medical Centre, 2017)
Introduction: Health care systems play a vital role in providing health services and in optimising the population’s health of each nation. The Malaysian health care system primarily consists of the public and private health services. One of the prominent private health care services offered in the General Practitioner’s (GP) Clinic. Despite the prominent role GPs play in the health care system in this country, little is known about their practices, the issues and challenges faced by GPs in this country. The objective of this study was to describe the current GP practice operations in Malaysia in terms of its general operations, financial expenditure and revenue, market competitiveness and laboratory services offered by the clinics. Methods: A cross-sectional survey design was used in this study. The study sample comprised of 1800 GPs throughout the West of Malaysia selected using convenient sampling technique. This study provides the general description of the GP operations in terms of the nature of business, operations hours, and number of patients, the third party administrator and managed care organisation linkages, financial expenditure, market competitiveness and laboratory services. Results: The findings of the study reveal that the expenditure of managing GP services has increased over the years due to the changes in policies as well as the involvement of third party administrators in the healthcare system despite it playing an instrumental role in complimenting the healthcare services for the public at large.